The Brownian motion process with generalized diffusion matrix and drift vector - Kopytko, B.I.; Novosyadlo, A.F. (Інститут математики НАН України, 2008)
Using the method of the classical potential theory, we have constructed a semigroup of operators that describes a multidimensional process of Brownian motion, for which the drift vector and the diffusion matrix are generalized functions.